Quality of Life and Associated Factors Among Family/Caregivers of Pediatric Patients Treated for Cancer at Tikur Anbessa Specialized Hospital: Institution-Based Cross-Sectional Study - Zenebe Negash MSc; Eden M. Kinfe BSc; Urji Zerihun BSc; Atalay M. Fentie MSc (Cancer Control)
Background Pediatric cancer significantly affects the quality of life (QOL) of patients and their families/caregivers particularly in low-income countries where there is scarcity of resources. Thus, the purpose of this study was to evaluate the QOL and associated factors among family/caregivers of pediatric patients treated for cancer at Tikur Anbassa Specialized Hospital (TASH), Addis Ababa, Ethiopia. Method An institution-based cross-sectional study design was used to collect information from family/caregivers who were present in the pediatric oncology unit at TASH from January 2, 2023 to May 30, 2023. The validated Amharic version of the caregiver oncology quality of life questionnaire (CarGOQOL) was used to collect the data. A random sampling technique was applied to select the study participants. The descriptive and regression analysis were conducted using statistical software SPSS version 27.0. Results A total of 350 family/caregivers answered the questionnaire. The overall response rate was 82.7%, and about 55% of the respondents were women. Among the participants, under-35 age made up the majority (60.9%). About 81% of family/caregivers were parents, and 77.7% of family/caregivers were married. More than half of the participants have at least a secondary level education. In addition, about two-thirds of the participants (63%) live in rural areas. Furthermore, more than half of the participants generate less than $17.86 per month. Nearly fifty percent of family/caregivers of pediatric cancer patients had poor QOL. The finding showed that widowed family/caregivers (AOR:5.59, 95%CI: 1.12, 27.79, P -value: 0.03) had poor QOL as compared to married, and those with a monthly income of between $17.87- $89.29 were less likely to have poor QOL compared to those with an income below <$17.87 ( P -value: 0.01). Conclusion In the current study, poor QOL was high among family/caregivers of pediatric cancer patients. Being widowed and lowest income were significantly associated with the QOL of the caregivers of pediatric patients with cancer.